Spectrophotometric determination of trace permanganate in water with N, N-diethyl-p-phenylenediamine (DPD). (December 2018) - Liu, Xin; Cai, Huahua; Zou, Jing; Pang, Zijun; Yuan, Baoling; Zhou, Zhenming; Cheng, Qingfeng
Abstract: A sensitive spectrophotometric method (the N, N -diethyl- p -phenylenediamine (DPD) method) was established for the determination of trace permanganate concentration (0–10 μM) in water. The DPD method was based on the oxidative coloration reaction where permanganate could oxidize DPD to form the red colored DPD radical (DPD + ) with a second-order rate constant of 2.96 × 10 4 M −1 s −1 at pH 6 (50 mM phosphate buffer). The generated DPD + could be quantitatively measured at 551 nm using an UV–Vis spectrophotometer. There was a good linear relationship (R 2 = 0.999) between the absorbance of DPD + and permanganate concentration. The DPD method was highly sensitive, and the absorbance of generated DPD + at 551 nm was as high as 5.70 × 10 4 cm −1 per M (mol L −1 ) of permanganate. The reaction of permanganate with DPD in the pH range of 4.0–8.0 had a stoichiometric coefficient of 1:2.71. The residual absorbance of DPD + in ultrapure water and natural waters was fairly stable for 30 min. Limits of detection of the proposed DPD method in ultrapure water and natural waters were calculated to be as low as 0.010 μM and 0.017 μM, respectively. Moreover, trace permanganate concentrations of 0.04 and 0.10 μM were found in natural waters and wastewater by the proposed DPD method. Additionally, the DPD method could be applied to measure the second-order rate constants of the reaction of permanganate with phenol at pH 7.0 (28.2 M −1 s −1 ). Graphical abstract: Highlights: The DPD method was based on the oxidative coloration of DPD by permanganate. The DPD method was accurate and sensitive for measuring trace permanganate concentration in natural waters and wastewater. The DPD method was effective in tolerating the interference of water matrix and colored substances. The DPD method could measure reaction rate constants of permanganate.